Collaborative model as a training for increasing village health worker competency about complementary feeding - Habibah Abidin; Apoina Kartini; Ani Margawati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: A Kader refers to a Village Health Worker (VHW), a volunteer, which becomes one of the sources of community reference. Commonly, they sustain a mother's knowledge regarding adequate complementary feeding. However, there are still some VHW who have not possessed a health education background nor been able to be independent.Objectives: This study aimed to analyze the impact of collaborative models on VHW's competence as in knowledge, self-efficacy, attitudes, and counseling skill on the topic of complementary feeding.Materials and Methods: The design of this research is a quasi-experiment control group pretest-postest, with the retrieval of subjects using purposive sampling. Subjects were selected based on the location of the posyandu. The population in this research was VHWs in the Lembang district were 40 VHWs in each group. The treatment group was given training intervention for 1 month with a collaborative model, combining several methods into a series. The main topic was counseling and complementary feeding. The control group was given booklets and leaflets. VHW's competence was measured using questionnaires. This research was conducted in January-April 2020.Results: Statistical test results before the treatment of both groups showed no difference (p>0,05) in each variable. Two months after the intervention, there were significant differensces in the mean score of knowledge (p=0,001), attitude (p=0,001), and VHWs self-efficacy (p=0,000) in both groups. VHW counseling skills (p=0,149) until the first month there was not a significant difference. Unexpectedly, in the second month, the VHW counseling skills could not be observed due to the global COVID-19 pandemic. The mean score of each group increased significantly, but the score of the treatment group was higher than the control group.Conclusions: A collaborative model is effective when compared to only providing booklets and leaflets in increasing VHW's knowledge, attitudes, and self-efficacy but not effective yet for VHW counseling skills.